FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI PADA WIRASWASTA USIA DEWASA DI KABUPATEN BOGOR: Faktor-Faktor yang Mempengaruhi Status Gizi Pedagang Makanan Usia Dewasa di Kabupaten Bogor - Nazila, Maulida Rochmatun; Sofianita, Nur Intania; Octaria, Yessi Crosita; Fauziyah, A'immatul (Universitas Airlangga, 2023)
Background: Overnutrition is becoming more common in Indonesia, with 13.5% of adults overweight and 28.7% obese. A lack of physical activity, excessive food consumption, and high consumption of risky foods such as sugar, salt, and fat are risk factors for nutritional status. Objectives: To determine the factors that influence the nutritional status of adult food traders in Bogor Regency. Methods: Researchers used a cross-sectional design in this study involving 99 food trader respondents aged 26-45 years using a convenience sampling method. Data collection started from January to May 2023. Nutritional status was measured using the Body Mass Index and then classified based on PGN 2014. Meanwhile, data on sugar, salt, and fat intake was collected using SQ-FFQ (Semi Quantitative Food Frequency Questionnaire) and PAL (Physical Activity Level) to determine the respondent's level of physical activity. Data analysis was using Fisher's test and logistic regression. Results: Based on Fisher's test analysis, there was a significant relationship between salt intake (p=0.041), physical activity (p=0.002), and food traders classification (p=0.000) with nutritional status. Meanwhile, no significant relationship was found between sugar and fat intake with nutritional status. The results of the logistic regression test showed that the most influential factor of nutritional status was excessive salt intake. Respondents with excessive salt intake had a 6.03 (95% CI=1.07-33.76) times higher risk of experiencing nutritional problems. Conclusions: There was a relationship between salt intake, physical activity, and food traders' classification with nutritional status. Meanwhile, there was no relationship between sugar and fat intake with nutritional status. The factor that most influenced the nutritional status of adult food traders in Bogor Regency was salt intake.